The Fund's Income Position for FY 2015 : Actual Outcome. (Policy Papers; Policy Paper ;, 2015)
This paper reports the Fund's income position for FY 2015 following the closing of the Fund's accounts for the financial year and completion of the external audit. FY 2015 net income, including income from surcharges, amounted to SDR 1.6 billion or about SDR 133 million more than estimated in April. The bulk of this difference reflects a smaller net loss in the valuation reported under the revised accounting standard for employee benefits (IAS 19). In accordance with decisions taken in April 2015, investment income from the Fixed-Income Subaccount of SDR 84 million has been transferred from the Investment Account to the GRA. GRA net income for FY 2015 of SDR 1.5 billion has been placed to the Fund's reserves, further strengthening the Fund's precautionary balances, which reached SDR 14.2 billion at the end FY 2015.